Shear bond strength of orthodontic brackets bonded to a new version of zirconium all ceramic restoration: An in vitro comparative study - Assem Abd EL-wahab; Marwa Shamaa; Ahmed Hafez; Noha El-Wassefy; Shaza Hammad (Heliyon, 2023)
Objectives: Esthetic restorations such as monolithic zirconia crowns are highly requested for adults nowadays. Bonding orthodontic braces on this type of material became a challenge for orthodontists, because of the special surface treatment needed. This study aims to assess the shear bond strength (SBS) of metal, and ceramic brackets bonded on two types of zirconia ceramics, surface roughness (SR) after different surface treatments for their surfaces, and adhesive remnant index (ARI). Materials and methods: Brackets’ base surface area (BSA) was scanned by an extra-oral scanner, then measured. The doubled labial surface of monolithic zirconia crowns (n = 30) and monolithic high translucent zirconia crowns (n = 30) were prepared and each was divided into three groups (n = 10) depending on surface treatment (hydrofluoric acid etching, no treatment, and rocatec airborne abrasion). Extracted lower central incisors (n = 20) were prepared. Each of them was divided into two subgroups depending on the type of bracket bonded on their surfaces (metal and ceramic). The SR, SBS, and ARI were assessed. Statistical analysis used: Tests used are independent-samples t-test, Fisher's exact test, One-Way ANOVA, and Kruskal-Wallis test. Results: The highest SBS and SR were observed in Enamel/Metal and Zirconia/Metal/Rocatec subgroups, respectively. Conclusion: Adequate bond strength could be obtained with the high translucent zirconia group if bonded with ceramic or metal brackets even if no treatment was used. Clinical significance: A proportion of simulation was done like practicing inside the dental clinic to reach the best results regarding the adhesion strength of orthodontic brackets.